Cybersecurity Risks: Are They Inflated? - Petr Chrapavy (Salus Journal, 2016)
With various views being posed on cybersecurity, this paper examines the proposition that cybersecurity risks are inflated. Due to the complexity of the cybersecurity environment, the risks will be dichotomised into two distinct categories—those posed by cybercrime, and those classified as cyber-warfare. In relation to cyber-crime, the paper examines the rise of cyber-crime, its costs, and the views of these factors by “alarmists” and “sceptics.” In relation to cyber-war, the paper sets aside the emotive issue of the consequences and focuses on the likelihood of a catastrophic attack. The paper concludes that the risk of cyber-crime is real, but the sometimes mooted existential threat poses by cyber-war is inflated. The paper argues that it is important for cyber defences to improve in line with the risks, and to do this, researchers need to work across both categories of cybersecurity.